Kif3a interacts with Dynactin subunit p150(Glued) to organize centriole subdistal appendages - Kodani, Andrew (European Molecular Biology Organization, 2013)
Formation of cilia, microtubule-based structures that function in propulsion and sensation, requires Kif3a, a subunit of Kinesin II essential for intraflagellar transport (IFT). We have found that, Kif3a is also required to organize centrioles. In the absence of Kif3a, the subdistal appendages of centrioles are disorganized and lack p150(Glued) and Ninein. Consequently, microtubule anchoring, centriole cohesion and basal foot formation are abrogated by loss of Kif3a. Kif3a localizes to the mother centriole and interacts with the Dynactin subunit p150(Glued). Depletion of p150(Glued) phenocopies the effects of loss of Kif3a, indicating that Kif3a recruitment of p150(Glued) is critical for subdistal appendage formation. The transport functions of Kif3a are dispensable for subdistal appendage organization as mutant forms of Kif3a lacking motor activity or the motor domain can restore p150(Glued) localization. Comparison to cells lacking Ift88 reveals that the centriolar functions of Kif3a are independent of IFT. Thus, in addition to its ciliogenic roles, Kif3a recruits p150(Glued) to the subdistal appendages of mother centrioles, critical for centrosomes to function as microtubule-organizing centres.